Sleep Health by Sexual Orientation among Women in the United States and Interrelations with Race/Ethnicity, Age, and Generational Cohort - Martinez-Miller EE; Gaston SA; Jackson II WB; Jackson CL (International Journal of Women's Health)
Erline E Martinez-Miller,1,2 Symielle A Gaston,3 W Braxton Jackson II,1 Chandra L Jackson3,4 1DLH, LLC, Bethesda, MD, USA; 2Department of Population and Data Sciences, University of Texas Southwestern Medical Center, Dallas, TX, USA; 3Epidemiology Branch, National Institute of Environmental Health Sciences, National Institutes of Health, Department of Health and Human Services, Research Triangle Park, NC, USA; 4Intramural Program, National Institute on Minority Health and Health Disparities, National Institutes of Health, Department of Health and Human Services, Bethesda, MD, USACorrespondence: Chandra L Jackson, Epidemiology Branch, the National Institute of Environmental Health Sciences, 111 TW Alexander Drive, Research Triangle Park, NC, 27709, USA, Tel +1 984-287-3701, Fax +1 301-480-3290, Email Chandra.Jackson@nih.govPurpose: To examine associations between sexual orientation and sleep; interrelations with race/ethnicity, age, and generation; and mediation by perceived sexual orientation discrimination among United States (US) women.Methods: Eligible Sister Study participants (N=50,790) identified as heterosexual or non-heterosexual at enrollment (2003– 2009), and self-reported sleep duration, sleep quality, and sleep mask and sleep medication use. We used latent class analyses to determine patterns of sleep health (good, moderate, poor). We investigated race/ethnicity, age, and generation as modifiers and perceived sexual orientation discrimination as a modifier and/or mediator. We used Poisson regression with robust variance to estimate prevalence ratios (PRs; 95% confidence intervals [CIs]) and inverse odds weighting to assess mediation.Results: Median age was 55 (interquartile range: 49– 62) years; 2% identified as non-heterosexual; 86% identified as non-Hispanic White, 9% non-Hispanic Black (NHB), and 5% Hispanic/Latina. Overall, sleep masks were more common among non-heterosexuals than heterosexuals (PR: 1.75 [95% CI: 1.17, 2.61]), and we did not identify other sexual orientation-sleep associations. Among NHB women, sleep medications were more prevalent among non-heterosexual orientation (1.54 [1.01, 2.35]). Among women who ever perceived discrimination, shorter than recommended duration was less common among non-heterosexuals than heterosexuals (0.78 [0.63, 0.96]) as was moderate sleep health compared to good sleep health (0.77 [0.63, 0.94]). Among women who never perceived discrimination, poor sleep health was more common among non-heterosexuals (1.29 [1.02, 1.63]).Conclusion: Prevalent sleep aid use among sexual minoritized women may help reduce sleep disparities by sexual orientation. Differential sleep experiences among intersecting identities can shape health inequities, and identification of mediating pathways can inform interventions.Plain Language Summary: Marginalization of non-heterosexual women may lead to poor sleep. Sexual orientation-sleep disparities have been documented; yet, few studies have evaluated multiple sleep measures or interrelations across social identities. We examined sexual orientation and self-reported sleep among women; intersections with race/ethnicity, age, and generation; and both mediation and moderation by perceived sexual orientation discrimination. Non-heterosexual, compared to heterosexual women were more likely to use sleep masks. Among non-Hispanic Black women, non-heterosexual women were more likely to use sleep medications than heterosexual women. Overall, perceived sexual orientation discrimination may modify associations between sexual orientation and both sleep health and sleep duration; perceived sexual orientation discrimination may also mediate the association between sexual orientation and sleep health. Women with intersecting disadvantaged identities experience unique stressors. Future studies should investigate objective sleep aid use over time, discrimination, and other mediating pathways.Keywords: epidemiology, women’s health, sexual minoritized, minority health, social discrimination